Potential of Phaeodactylum tricornutum for biodiesel production under natural conditions in Chile - Teresa M. Mata (2018)
: Diatoms are very diverse and highly productive organisms, found in a wide variety ofenvironments. This study aims to analyze the growth and lipid composition of Phaeodactylum tricornutum,cultured in an outdoor pilot-scale bubble column photobioreactor under natural conditions in Chile forbiodiesel production. Results showed that P. tricornutum cultures reached their highest biomassconcentration (0.96 ± 0.04 kg m−3) after 14 days of culturing, at the stationary phase, with avolumetric productivity of 0.13 kg m−3 d−1. Biomass samples showed a total lipid content of9.08 ± 0.38 wt %. The fatty acid methyl ester analysis revealed a composition of 24.39% C16-C18 fattyacids, 42.34% saturated fatty acids, 21.91% monounsaturated fatty acids and 31.41% polyunsaturatedfatty acids. These findings suggest that P. tricornutum oil can be used as an alternative raw materialfor the production of biodiesel capable of meeting international quality standards.